English Students Perception Towards the Implementation of Online Learning at SMPN 1 Selemadeg - Suantara, I Putu Dika Adi (English Education Department STKIP Agama Hindu Singaraja, 2023)
This study aimed to investigate students' perceptions of the implementation of online learning for English subjects at SMP Negeri 1 Selemadeg in the academic year of 2021/2022. This study was a quantitative study using a cross-sectional survey design. There were 217 seventh-grade students at SMP Negeri 1 Selemadeg, Tabanan Regency who participated in this study. There were 25 items on 3 questionnaires that were adapted to the study and used as data collection instruments. Students' perceptions were seen from the three dimensions of Technology Acceptance Model 3 (TAM3), namely Perception of Usefulness, Perception of Ease of Use, and Behavioural Intentions. This study found that 4 determinants that were positively qualified and 5 were positively qualified. It was revealed that the seventh-grade students of SMP Negeri 1 Selemadeg thought that learning English can be done online using the WhatsApp, Google Meet, and Google Classroom applications to improve English performance and be easy to use. Thus, taking advantage of online learning with the right applications is an important consideration for teachers in their classrooms.